"Stuttering - Poisson" distributions - Kemp, C. D. (Statistical and Social Inquiry Society of Ireland, 1967)
' Stuttering-Poisson' (Galliher et al.) aptly describes a very general class of discrete distributions which appears under a variety of names in the literature and which has many practical applications in operational research, e.g. in queueing and inventory problems.
Read before the Society, 1 May 1967
Keywords: Stuttering Poisson distributions; Inventory models; Queueing models; 314.15